Big Data Challenges - Definition, Characteristics and Technologies - Yordanova, Stanimira; Stefanova, Kamelia (Research Papers, 2019)
Volume, complexity, variety and velocity of generated data today reach incredible levels and data cannot be collected, selected, processed or managed through widely used and applied software tools. The need to extract meaningful information from big data evokes the development of new approaches and technologies for storing, processing and analyzing big data coming from different sources. This paper aims to present the definition, characteristics and technologies for storing and managing big data that require a new approach to understanding data and information.